Host Cell Participation in Small Virus Replication I. Replication of M-13 in a Strain of Escherichia coli with a Temperature-sensitive Lesion in Deoxyribonucleic Acid Synthesis - Primrose, S. B. (1968)
The replication of M-13 in a strain of Escherichia coli with a thermosensitive lesion in deoxyribonucleic acid synthesis was studied. M-13 failed to replicate at the restrictive temperature, even when the parental replicative form was allowed to form at the permissive temperature. When cells which were actively producing phage at the permissive temperature were shifted to the restrictive temperature, phage production continued. The incorporation of radioactive label into phage particles at 42 C indicated that continued single-strand synthesis was unaffected by the lesion in the host cell.